2017
DOI: 10.1021/acscatal.7b00426
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO-Catalyzed Electrochemical C–H Thiolation: Synthesis of Benzothiazoles and Thiazolopyridines from Thioamides

Abstract: Benzothiazoles and thiazolopyridines are widely prevalent in pharmaceuticals and organic materials. Herein, we report a metal-and reagent-free method for the uniform synthesis of benzothiazoles and thiazolopyridines through 2,2,6,6-tetramethylpiperidine-N-oxyl radical (TEMPO)-catalyzed electrolytic C−H thiolation. This dehydrogenative coupling process provides access to a host of benzothiazoles and thiazolopyridines from N-(hetero)arylthioamides. Mechanistic studies suggested that the thioamide substrate was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(97 citation statements)
references
References 64 publications
0
94
0
3
Order By: Relevance
“…Based on the above studies and previous reports, a possible mechanism for the electrochemical cyclization reaction was proposed using carbamate 30 as a model substrate (Scheme ). At the anode, TEMPO ( E p/2 = 0.67 V vs .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above studies and previous reports, a possible mechanism for the electrochemical cyclization reaction was proposed using carbamate 30 as a model substrate (Scheme ). At the anode, TEMPO ( E p/2 = 0.67 V vs .…”
Section: Resultsmentioning
confidence: 99%
“…301 Although the thiophenol can also be oxidized to the corresponding disulfide under the reaction conditions, it was believed that the aryl radical cation could engage the disulfide or the intermediary sulfur-centered radical to afford the thiolation product. An intramolecular thiolation process has been devised by Lei to synthesize benzothiazoles from aryl-isothiocyanate electrochemically (Figure 18E)—this reaction presumably occurs through the intermediacy of a sulfur-centered radical; 302,303 …”
Section: Anodic Oxidationmentioning
confidence: 99%
“…[52] Xu et al reported an elegant synthesis of benzothiazoles from thioanilides.Inanundivided cell under constant-current conditions,many different functional groups and substitution patterns were tolerated (Scheme 44). [135] Thea uthors again confirmed that this was av aluable alternative to classic synthetic routes,a nd that this method can be used to generate natural products or drugs more efficiently.Asimilar substrate underwent the same cyclization reaction. [136] When amidine functional groups were oxidized at the anode,t he generated amidinyl radicals underwent cyclization with the attached aromatic ring system (Scheme 45).…”
Section: Electrochemical Synthesis Of Heterocyclesmentioning
confidence: 69%
“…TEMPO-mediated synthesis of benzothiazoles. [135] Scheme 45. Electrochemical generation of benzimidazoles and pyridoimidazoles.…”
Section: Electrochemical Synthesis Of Heterocyclesmentioning
confidence: 99%